Financial Performance Analysis Before and After the Initial Public Offering (IPO) - Linda Novita Dewi; Dicky Jhoansyah; Kokom Komariah (Program Studi Manajemen, Fakultas Ekonomi, Universitas Langlangbuana, 2020)
During the 2014 presidential election, the performance of the property sector, real estate, and construction of national buildings reached 55.76%. However, in the following year, the performance of the property, real estate, and building construction sector declined and continued until 2018. Therefore many companies from this sector decided to take the floor on the Indonesian stock exchange. with this, it is hoped that the financial performance of this sector will improve. The purpose of this study was to determine whether there was an increase or not in the financial performance of the property, real estate, and building construction sector which was conducted in IPO 2017 on the Indonesia stock exchange. The research method used in this study is quantitative. The sampling technique used was purposive sampling technique with predetermined criteria. and obtained four companies selected as research samples. Data analysis techniques used in this study are horizontal analysis with liquidity ratios, activities, solvency, and profitability ratio. the results of this study are there is an increase in financial performance after the IPO with solvency ratios and there is a decrease in financial performance after IPO with liquidity ratios, activity ratios, and profitability ratios